Vaccination in pregnancy: Attitudes of nurses, midwives and health visitors in England - Bhavita Vishram; Louise Letley; Albert Jan Van Hoek; Louise Silverton; Helen Donovan; Cheryll Adams; David Green; Angela Edwards; Joanne Yarwood; Helen Bedford; Gayatri Amirthalingam; Helen Campbell (Taylor & Francis Group, 2018)
Objective: To examine amongst healthcare professionals in England; knowledge of vaccinations in pregnancy, their perceived roles in these programmes and whether they recommend scheduled vaccines to pregnant women. Design: Cross sectional survey (online questionnaire) Setting: Healthcare workers in contact with pregnant women in England. Participants: The survey analysis included 3441 healthcare workers who had been surveyed during May to August 2015. The participants were midwives, practice nurses and health visitors, working in England who were members of the Royal College of Midwives, Royal College of Nursing and the Institute of Health Visiting. Results: We found that knowledge of vaccination in pregnancy was high in all professional groups. Seventy three percent of all respondents would recommend the influenza vaccine and 74% would recommend the pertussis vaccine to pregnant women. They were more likely to recommend vaccination in pregnancy if they would personally have the influenza and pertussis vaccines themselves and/or if they had the influenza vaccine as a healthcare worker. Practice nurses were significantly more likely to recommend the pertussis and influenza vaccines to pregnant women than midwives and health visitors. Health professionals who had received immunisation training were more confident in giving advice to pregnant women. Conclusion: Immunisation training is essential if healthcare workers are to be informed and confident in effectively delivering the maternal immunisation programme and thus improving uptake of vaccines in pregnancy. These findings are important in tailoring educational programmes and addressing the training needs of different healthcare professional groups.